Effects of Honey Bee Race and Season on Propolis Composition - Merve Keskin; Meral Kekeçoğlu; Ceren Birinci; Esra Birinci; Sevgi Kolaylı (Journal of Agricultural Sciences)
Honey bees collect the main material of propolis from the buds, leaves, branches, and barks or other botanical sources and mixed that resinous material with beeswax produced from abdominal exocrine glands, mandibular gland secretions, and pollen to produce propolis. The composition of propolis changes depends on multiple factors such as honey bee races, geographical locations, phytogeography, harvesting seasons, extraction methods and solvents. In this study, two different studies were conducted in two different locations in order to reveal the effect of race and season variables on the composition and antioxidant value of propolis. The effect of race factor was studied on three different honey bee races (Apis mellifera caucasica, Apis mellifera syriaca and Apis mellifera carnica) and two different ecotypes (Muğla ecotype and Yığılca ecotype) to investigate the effects of race factor on propolis composition in Central Anatolia by under the controlled conditions. The effect of seasonal change was determined by Yığılca ecotype of A. melifera anatoliaca in the apiary located in Yığılca, Düzce location. Studied samples were harvested by propolis trap between May and October. Total phenolic content, total antioxidant capacity and chemical profiles of propolis samples were determined using HPLC-UV. The obtained results showed that honey bee race and season have an effect on the antioxidant capacity and chemical composition of propolis.